THE INFLUENCE OF HALAL LABEL, KOREAN WAVE, AND HALAL AWARENESS ON THE PURCHASE INTEREST IN KOREAN FOOD AMONG GENERATION Z - Susilowati, Lantip; Novitasari, Emi Salsa (Faculty of Islamic Economic and Business - Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
Abstract: Global phenomena are driving changes in Generation Z's consumption patterns, including an increased interest in Korean food influenced by the Korean wave. This is evident from the proliferation of Korean food outlets in various cities. However, in the context of Muslim communities, halal labels and halal awareness are important factors in purchasing decisions. The purpose of this study is to analyze the influence of halal labels, the Korean wave, and halal awareness, both simultaneously and partially, on the purchasing interest of Korean food among Generation Z. This study uses a quantitative method with an associative research type. The population in this study is Generation Z who have consumed Korean food with a sample of 385 respondents. The sampling method is nonprobability sampling with a purposive sampling technique and data collection using a questionnaire. Data analysis in this study uses multiple linear regression analysis with SPSS version 27. The results show that halal labels, the Korean wave, and halal awareness, both simultaneously and partially, have a positive and significant effect on the purchasing interest of Korean food among Generation Z. Keywords: Purchase Interest; Halal Label; Korean wave; Halal awareness. Abstrak: Fenomena global mendorong perubahan pola konsumsi Generasi Z, termasuk meningkatnya minat terhadap Korean food yang dipengaruhi oleh Korean wave. Tampak dari menjamurnya gerai Korean food di berbagai kota. Namun, dalam konteks masyarakat muslim, label halal dan halal awareness menjadi faktor penting dalam keputusan pembelian. Tujuan Penelitian ini adalah untuk menganalisis pengaruh label halal, Korean wave, dan halal awareness baik secara simultan maupun secara partial terhadap minat beli Korean food pada generasi Z. Penelitian ini menggunakan metode kuantitatif dengan jenis penelitian asosiatif. Populasi dalam penelitian ini yaitu generasi Z yang pernah mengkonsumsi makanan korea dengan jumlah sampel sebanyak 385 responden. Metode dalam pengambilan sampel adalah nonprobability sampling dengan teknik purposive sampling dengan teknik pengumpulan data menggunakan kuesioner. Analisis data dalam penelitian ini menggunakan analisis regresi linear berganda dengan alat bantu SPSS versi 27. Hasil penelitian menunjukkan bahwa label halal, Korean wave, dan halal awareness baik secara simultan maupun partial berpengaruh positif dan signifikan terhadap minat beli Korean food pada generasi Z. Kata Kunci: Label halal; Korean wave; Halal Awareness; Minat Beli.